Pengaruh Citra Merek , Harga dan Kualitas Produk Terhadap Minat Beli Produk Sunscreen - Rahma Fitriani Thalitha; Supriyanto Supriyanto; Dody Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
The development of products, especially the front part, is one part that can support the appearance and become a mandatory requirement for every woman. Consumer products, especially those who want to travel to campus, are more selective in choosing the latest products, especially The Originote sunscreen for consumers. This study was conducted to determine simultaneously and partially the independent variables, namely Brand Image, Price, and Product Quality, the dependent variable Purchase Interest. The method used in this study uses a quantitative method, where in this study using Purposive Sampling calculations with the Hair formula. The entire population in this study was 100 respondents. Based on the results of the study in the partial test (T) that the variable of brand image affects purchase interest. for the price variable affects purchase interest. the product quality variable affects purchase interest. Furthermore, in the simultaneous test of brand image, price and product quality affect purchase interest. This explains that there is a contribution of brand image, price, product quality to purchase interest.